Characteristics of Hypertension Patients in the Lansilowo Community Health Center Work Area, Konawe Islands Regency - Lisa Lisa; Nana Andriani; Rahmatia Rahmatia (Journal of Epidemiology and Health Science, 2026)
Background : Hypertension is​ partly disease Chronic hypertension is a major factor in morbidity and mortality worldwide. This condition is known as a silent killer because it often occurs without symptoms, but can lead to dangerous complications such as stroke, heart failure, and chronic kidney disease. In Indonesia, the prevalence of hypertension continues to increase annually, including in the Lansilowo Community Health Center (Puskesmas Lansilowo) area, which recorded the highest number of cases among the top 10 diseases in 2023. Objective : Study This aim For Understanding the characteristics of hypertension patients based on gender, age and employment status in the working area of the Lansilowo Health Center, Konawe Islands Regency in 2024. Method: Study This is study A descriptive study using a survey approach. Using the total sampling technique, all 129 patients recorded in the 2024 profile were sampled. Results: Results from studies This showed that the majority of patients suffering from hypertension were women, namely 85 people (65.9%), while male patients numbered 44 people (34.1%). When viewed in terms of age, the largest group was in the 46-55 year range with a total of 49 people (38.0%), followed by the 56-65 year age group which numbered 38 people (29.5%). In terms of occupation, most of the patients were women who worked as housewives (IRT) as many as 70 people (54.3%), followed by farmers 28 people (21.7%) and self-employed 18 people (14.0%). Conclusion: In conclusion, hypertension in the Lansilowo Community Health Center's work area is predominantly found in middle-aged women who work as housewives. This finding demonstrates the importance of health education, early detection, and lifestyle changes in high-risk groups, especially women aged over 40 years. Promotive and preventive efforts need to be strengthened through routine screening programs and counseling at the health facility and community levels. Keywords: Hypertension, Patient Characteristics, Gender, Age, Occupation, Community Health Center